2003
DOI: 10.1074/jbc.m211719200
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of β3 Subunit Incorporation on the Pharmacology and Single Channel Properties of Oocyte-expressed Human α3β4 Neuronal Nicotinic Receptors

Abstract: We compared the main properties of human recombinant ␣3␤4␤3 neuronal nicotinic receptors with those of ␣3␤4 receptors, expressed in Xenopus oocytes. ␤3 incorporation decreased the channel mean open time (from 5.61 to 1.14 ms, after approximate correction for missed gaps) and burst length. There was also an increase in single channel slope conductance from 28.8 picosiemens (␣3␤4) to 46.7 picosiemens (␣3␤4␤3; in low divalent external solution). On the other hand, the calcium permeability (determined by a reversa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…Rat ␣3␤4 receptors expressed in BOSC 23 cells predominantly shows a 34-pS conductance class (Ragozzino et al, 1997). Overall, our findings are similar to the previously published single-channel data on wild-type ␣3␤4 and ␣3␤4␣5 receptors (e.g., Nelson and Lindstrom, 1999;Boorman et al, 2003). Our single-channel data indicate that the ␣5(Asp398) and ␣5(Asn398) variants behave similarly in single-channel recordings.…”
Section: Decay Timesupporting
confidence: 81%
“…Rat ␣3␤4 receptors expressed in BOSC 23 cells predominantly shows a 34-pS conductance class (Ragozzino et al, 1997). Overall, our findings are similar to the previously published single-channel data on wild-type ␣3␤4 and ␣3␤4␣5 receptors (e.g., Nelson and Lindstrom, 1999;Boorman et al, 2003). Our single-channel data indicate that the ␣5(Asp398) and ␣5(Asn398) variants behave similarly in single-channel recordings.…”
Section: Decay Timesupporting
confidence: 81%
“…␤3 subunits do not drastically alter the EC 50 for ACh or nicotine when incorporated into nAChRs (Boorman et al, 2003), but they do profoundly alter single-channel kinetics (Boorman et al, 2003). Channel burst duration was significantly shortened for nAChRs containing ␤3 versus those without it (Boorman et al, 2003), suggesting that ␤3 reduces the probability of channel opening, P open .…”
Section: P379mentioning
confidence: 99%
“…␤3 also increases ␣6-specific binding activity in HEK293 cells (Tumkosit et al, 2006). Uncertainty exists, however, because others have reported that ␤3 incorporation into nAChRs acts as a dominant negative (Boorman et al, 2003;Broadbent et al, 2006), suppressing ACh-evoked responses by an incompletely understood gating mechanism. This effect occurred apparently without significantly altering the surface expression of nAChRs.…”
mentioning
confidence: 99%
“…V273T subunits participate in formation of ␣3␤4*-nAChR (23,24), help to define nAChR subtypes capable of containing ␤3 subunits, thus providing insights into roles of ␤3*-nAChR in nicotinic signaling. However, there remain puzzles about the makeup of functional, all-human or all-mouse ␣6*-nAChR, especially ␣6␤3*-nAChR.…”
Section: V13јsmentioning
confidence: 99%